The Structured Innovation System: Optimizing Patent Filing and Obtaining Global Protection - Raymond R. Tjandrawinata; Henry Soelistyo Budi (Riviera Publishing, 2025)
Intellectual property (IP) is a key component of the global economy, and it is also a critical component of ensuring global competitiveness. It is essential for organizations and inventors seeking robust global intellectual property protection to maintain competitive advantage. This study examines the role of structured innovation in enhancing patent approval rates, mitigating legal risks, and accelerating market entry for technological innovations. The study employs a mixed-methods approach, integrating legal analysis, case study evaluations, empirical data collection, and AI-based predictive modeling to provide an in-depth understanding of the factors contributing to successful patent filings and long-term intellectual property sustainability. The research also examines emerging trends in artificial intelligence and predictive analytics that are reshaping the landscape of IP management. The findings derived from this study serve as a valuable resource for policymakers, legal practitioners, and industry stakeholders seeking to enhance their innovation strategies in an increasingly competitive and complex intellectual property landscape. Specifically, this study aims to provide a strategic roadmap for optimizing patent filing and securing global protection by evaluating real-world applications and examining cross-jurisdictional intellectual property frameworks. A comparative study of patent laws across key jurisdictions, including the United States, the European Union, and China, highlights critical differences in examination procedures, enforceability, and litigation risks, providing comparative insights essential for businesses operating in global markets. The empirical findings underscore that structured innovation methodologies contribute to higher patent success rates and reduce legal uncertainties, enforcement complexities, and post-grant challenges.